Caregiver Burden and Associated Factors Among Informal Caregivers of Stroke Survivors. Issue 6 (December 2020) - Achilike, Saviour; Beauchamp, Jennifer E. S.; Cron, Stanley G.; Okpala, Munachi; Payen, Samuel S.; Baldridge, Lyric; Okpala, Nnedinma; Montiel, Tahani Casameni; Varughese, Tina; Love, Mary; Fagundes, Christopher; Savitz, Sean; et al.
Abstract : ABSTRACT: BACKGROUND: Informal caregiving of stroke survivors often begins with intensity compared with the linear caregiving trajectories in progressive conditions. Informal caregivers of stroke survivors are often inadequately prepared for their caregiving role, which can have detrimental effects on their well-being. A greater depth of understanding about caregiving burden is needed to identify caregivers in most need of intervention. The purpose of this study was to examine caregiver burden and associated factors among a cohort of informal caregivers of stroke survivors. METHODS: A cross-sectional study of 88 informal caregivers of stroke survivors was completed. Caregiver burden was determined with the Zarit Burden Interview, caregiver depressive symptoms were measured with the Patient Health Questionnaire-9, and stroke survivor functional disability was assessed with the Barthel Index. Ordinal logistic regression was used to identify independent factors associated with caregiver burden. RESULTS: Forty-three informal caregivers (49%) reported minimal or no caregiver burden, 30 (34%) reported mild to moderate caregiver burden, and 15 (17%) reported moderate to severe caregiver burden. Stroke survivor functional disability was associated with informal caregiver burden ( P = .0387). The odds of having mild to moderate caregiver burden were 3.7 times higher for informal caregivers of stroke survivors with moderate to severe functional disability than for caregivers of stroke survivors with no functional disability. The presence of caregiver depressive symptoms was highly correlated with caregiver burden ( P < .001). CONCLUSION: Caregivers of stroke survivors with functional disabilities and caregivers experiencing depressive symptoms may have severer caregiver burden. Trials of interventions aimed at decreasing informal caregiver burden should consider the potential impact of stroke survivors' functional disability and the presence of depressive symptoms. Abstract : Supplemental digital content is available in the text.